Reduced temperature electrical measurement of semiconductor devices - Ang, Derrick Jia Hao (2015)
This report introduce the research status of thermoelectric cooling on semiconductors such as diode and semiconductor wafer. Measurement of current-voltage characteristic of semiconductor diodes by applying thermoelectric cooling device to determine how temperature affects its quality and operation. In addition, experiments are conducted on epitaxial silicon-germanium wafers on hot plate and by applying thermoelectric cooling device to determine the effect of thermal dissipation using Fourier’s law to show the effect of thermoelectric cooling. Measurement results and findings of the experiments will be discussed in detail in this report.